Clinical, mechanical, and immunohistopathological effects of tissue adhesives on the colon: An in‐vivo study. Issue 4 (24th January 2016) - Vakalopoulos, Konstantinos A.; Wu, Zhouqiao; Kroese, Leonard F.; van der Horst, Paul H.; Lam, King H.; Dodou, Dimitra; Jeekel, Johannes J.; Lange, Johan F.
Abstract: Background: Tissue adhesives may be useful for sealing bowel anastomoses by preventing anastomotic leakage. Prior to clinical implementation, an in‐depth analysis of the clinical and immunohistopathological effects of tissue adhesives on the target tissue and of the mechanical strength of the adhesive bond in an in vivo model is needed. Materials and methods: In 84 rats, two bowel segments were glued using one of the following tissue adhesive: Bioglue, Gelatin‐resorcinol‐formaldehyde (GRF), Glubran 2, Histoacryl Flex, Omnex, Duraseal Xact, or Tissucol. Rats were followed for 7 or 28 days. Endpoints were clinical complication rate, mechanical strength, and immunohistopathological reactions. Results: Of the seven tissue adhesives, GRF and Bioglue showed the highest rates of bowel wall destruction and ileus and the most severe immunohistopathological tissue reactions at 7 and 28 days. Cyanoacrylates (Histoacryl Flex, Omnex, Glubran 2) showed high mechanical strength and mild immunohistopathological reactions at 7 and 28 days. Duraseal Xact and Tissucol were the most inert tissue adhesives, but exhibited low mechanical strength. At 28 days, mechanical strength was significantly correlated to CD8, CD68, and Ki67 cell counts. Conclusion: Based on the clinical and immunohistopathological outcomes, GRF and Bioglue were found to be the least suitable tissue adhesives for colonic use. Duraseal Xact and Tissucol were inert but also showed low mechanical strength. Cyanoacrylates exhibited mild clinical and immunohistopathological effects while maintaining high strength, which makes them promising as colonic sealants. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 846–854, 2017.